1994
DOI: 10.1111/j.1745-4549.1994.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

QUALITY LOSS of DOUBLE CONCENTRATED TOMATO PASTE: EVOLUTION of the MICROBIAL FLORA and MAIN ANALYTICAL PARAMETERS DURING STORAGE AT DIFFERENT TEMPERATURES

Abstract: This study deals with nonsterile canning of double concentrate tomatoes (30° Brix) stored for 210 days at three different temperatures (4, 10 and 25C) in 200 kg drums. the evolving analytical composition (soluble solids, total solids, glucose, fructose, pH, total acidity, volatile acidity, citric acid, malic acid, succinic acid, hydroxymethylfurfural (HMF) and color parameters) that the product underwent during storage was dependent both on storage temperature and on different aerobic levels within the drum (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…The work of Eliot et al (1998) on shredded mozzarella cheese under modified atmosphere also indicated that initial psychrotrophic count 4.36 log cfu/g increased to 7.00 log cfu/g after 3 weeks of storage. The results match with the findings of Villari et al (1994) who observed that the psychrotrophic organisms were less numerous when stored in high CO 2 atmospheres in case of refrigerated pizza. Finally, the counts of anaerobic spore formers were also low (< 3 log cfu/g) and show increasing trend in all pizza samples with anaerobic conditions and slight decrease in air packed pizza samples throughout the entire storage period (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The work of Eliot et al (1998) on shredded mozzarella cheese under modified atmosphere also indicated that initial psychrotrophic count 4.36 log cfu/g increased to 7.00 log cfu/g after 3 weeks of storage. The results match with the findings of Villari et al (1994) who observed that the psychrotrophic organisms were less numerous when stored in high CO 2 atmospheres in case of refrigerated pizza. Finally, the counts of anaerobic spore formers were also low (< 3 log cfu/g) and show increasing trend in all pizza samples with anaerobic conditions and slight decrease in air packed pizza samples throughout the entire storage period (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The results also confirm the earlier findings of Alves et al (1996);Fedio et al (1994); Eliot et al (1998);Alam (2004), who while working on MAP of mozzarella cheese observed that CO 2 had bactericidal effect Of the facultative anaerobic bacterial species, LAB constituted part of the natural microflora of baked pizza samples stored in air and under MAP (Fig. 1b) probably originating from pizza ingredients such as cheese (Eliot et al, 1998) and tomato paste (Villari et al, 1994). Coliforms also found in the pizza samples but to a lesser degree may be due to cross contamination and their contribution is significant only for samples stored under aerobic conditions (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Wiese and Dalmossa (32) also reported increases in organic acids (lactic acid, malic acid, citric acid, and pyrocarboxylic acid) after processing of tomato juice. Villari et al (33), however, reported decreases in organic acids with increased storage time and temperature of tomato paste. They also reported a decrease in pH and increase in the acidity during storage of tomato juice.…”
Section: Homogenizationmentioning
confidence: 96%
“…Wiese and Dalmasso (32) reported significant increase in the hue angle of tomato juice after processing and storage, indicating loss of red color. Color retention in tomato products is better at lower temperature (33,34). The main cause of carotenoid degradation in foods is oxidation.…”
Section: Atmentioning
confidence: 99%
“…Wiese and Dalmasso (1994) reported an increase in the hue angle of tomato juice after processing and storage, indicating a loss of red color. The color retention in tomato products is better at lower temperatures (Sherkat and Luh, 1976;Villari et al, 1994).…”
Section: Lycopene Stability During Tomato Processingmentioning
confidence: 98%